Ignition characteristics of 1-Nitropropane: Experimental measurements and kinetic modeling. (1st June 2022) - He, Li; Li, Chong; Shang, Yanlei; Ning, Hongbo; Shi, Jinchun; Luo, Sheng-Nian
Abstract: 1-nitropropane (1-NP), a potential advanced propellant and a fuel additive, is considered as a suitable surrogate for understanding the combustion properties of nitro-alkanes. Here, the ignition characteristics of 1-NP/O 2 /Ar are investigated at the pressures of 4–20 atm, the equivalence ratios of 0.5–2, and the temperatures of 910–1790 K in a heated shock tube. The ignition delay time of 1-NP increases with decreasing pressure and increasing equivalence ratio. The pressure effect is more pronounced at high temperature, while the effect of equivalence ratio is insignificant at the dilution level of 95.75% Ar. The rate constants of the important unimolecular decomposition reactions of 1-NP are calculated at 500–2000 K and 0.0001–100 atm, and a new 1-NP model is proposed based on our calculations and the nitromethane model by Shang et al.. The new model has a good performance in predicting the measured ignition delay times of 1-NP but gives an overestimation under the fuel-rich condition with a dilution level of 95.75% Ar. The kinetic analyses are carried out to elucidate the ignition mechanism of 1-NP and the defects of the model. The results indicate that the C–N bond fission reaction is the dominant pathway consuming 1-NP, and the reactions involving NO x control the ignition process. Ethylene and propylene are the key intermediates, and further work on the reactions between NO and the species related to the degeneration of alkene is necessary to complete the combustion model of 1-NP. Highlights: Ignition delay times of 1-nitropropane are reported for the first time. Pressure- and temperature-dependent rate constants for the 1-nitropropane unimolecular reactions are calculated. A new combustion model is proposed based on the calculations and validated against the measurements. Kinetic analyses are implemented to interpret the ignition mechanism of 1-nitropropane.